Berechenbarkeit der Welt. - Bonner Kunstverein, Bonn; Pohlen, Annelie (Bonn : Bonner Kunstverein, 1996)
Boetti, Alighiero ; Blum, Heiner ; Van Caeckenbergh, Patrick ; Darboven, Hanne ; Dion, Mark ; Ecker, Bogomir ; Höller, Carsten ; Huber, Felix Stephen ; Hyber, Fabrice ; Kawara, On ; Lempert, Jochen ; McCaslin, Matthew ; Mields, Rune ; Opalka, Roman ; Trockel, Rosemarie ; Wisniewski, Jeffrey
bibliografie
biografie
Berechenbarkeit der Welt, Bonner Kunstverein, Bonn, 15.5. - 21.7.1996
Duits
Engels
boek